Mis-selling of financial products and investors enforcement mechanism-whither Malaysia? - Mohd. Sulaiman, Aiman @ Nariman (2017)
Numerous scandals revolving around financial products have ignited concerns in various jurisdictions about the adequacy of investor protection in the financial services industry. In some jurisdictions, regulators have stepped into the shoes of the aggrieved investors , followed by investors' initiated private actions. Law reform exercises have focused on legal mechanisms that goes beyond the traditional private law enforcement to include important statutory liability and enforcement mechanism, and enforceable by regulatory authorities, leading to a more interventionist approach by regulators. Financial products mis-selling , ranging from pensions mis-selling, payment protection insurance, structured investment products , amongst others, are some of the more long term investment products receiving much-deserved scrutiny in various jurisdictions, primarily because of their to impact on the masses. The article discusses the enforcement mechanisms in Malaysia in view of the newly introduced Financial Services Act 2013 to assess the (in)adequacy of the public and private enforcement mechanisms.